The quality difference in five oolong tea accessions under different planting management patterns in south Fujian of China - He, Huanzhu; Jiang, Yuhang; Su, Chengjia; Min, Qingwen; Wu, Weikun; Xie, Kexiao; Yue, Liang; Chen, Zhidan; Lin, Wenxiong; Yi, Pyong-In (Frontiers in Agronomy, 2024)
Introduction Oolong tea, celebrated for its significance in Chinese tea culture, was the subject of investigation in this study. Methods Five varieties of Minnan oolong tea were sampled, each cultivated under two distinct management approaches: conventional management and natural growth methods. The study aimed to discern variations in sensory attributes, encompassing appearance and liquor color, alongside the analysis of chemical composition. Results and discussion The results indicated that oolong tea cultivated through conventional manual management generally exhibited qualities in terms of shape and foliage appearance, in contrast to those grown naturally. However, naturally grown oolong tea tended to exhibit more favorable aroma and taste profiles compared to conventionally managed counterparts. Furthermore, the content of water extract, amino acids, polyphenols, caffeine, and other pivotal chemical constituents were typically higher in naturally grown tea varieties compared to conventionally managed ones. Conversely, catechin content was found to be more abundant in traditionally managed bushes than in those grown naturally. These findings emphasize the significance of implementing appropriate natural growth management practices to enhance the quality of Minnan oolong tea and maintain ecological sustainability.